Designing Youth Center in Medan City with Green Architecture Approach - Rahman, N. Vinky; Putri, Annisa (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Medan, a major city in Indonesia, has a substantial youth population. To foster positive development and prevent negative activities among adolescents, a dedicated space is essential. Hence, the Youth Center was established to create a comfortable and quality environment where youths can develop their talents and skills. The Youth Center offers sports, arts, and other supportive facilities designed to promote positive activities. Its main goal is to enhance the capabilities and potentials of adolescents, aiming to cultivate a responsible and high-quality younger generation through its facilities and programs.